Enhanced degradation performance of organic dye over the reduced double perovskite compound Sr2CaWO6 under visible light irradiation. (31st May 2019) - Wang, Xianxian; Ge, Xiaoli; Liu, Xin; Song, Xiaoyu; Xu, Xuewen
Abstract: We investigated the effects of heat treatment in reduced atmosphere on the chemical states and photocatalytic performance of a typical double perovskite compound, Sr2 CaWO6 . The pristine Sr2 CaWO6 powders, prepared with a simple sol-gel method, crystallize in a monoclinic structure. The as-prepared Sr2 CaWO6 powders were treated at 900, 1000 and 1100 °C in flowing H2 atmosphere to obtain photocatalyst samples. The main phase composition of the reduced samples is in accordance with that of the pristine sample. X-ray photoelectron spectra analysis confirmed that the reduced treatment at 1100 °C introduced a great quantity of sub-stoichiometric species (including W 5+ or W 4+, O − or O atom) and oxygen vacancies in the photocatalyst. The first principle calculations were performed to study the electronic structures of the Sr2 CaWO6 with the intrinsic defects. The black sample treated at 1100 °C can absorb visible light efficiently, and exhibits superior photocatalytic activity and stability on degradation of methyl orange. The main active species for the decolorization of methyl orange are · O 2− and h + radicals.